2016
DOI: 10.18632/oncotarget.7959
|View full text |Cite
|
Sign up to set email alerts
|

Oral isoflavone supplementation on endometrial thickness: a meta-analysis of randomized placebo-controlled trials

Abstract: BackgroundIsoflavone from soy and other plants modulate hormonal effects in women, and the hormone disorder might result in different caners including endometrial cancer. However, it's effect on the risk of endometrial cancer is still inconclusive. We aimed to assess the effects of isoflavone on endometrial thickness, a risk factor of endometrial cancer in peri- and post-menopausal women.MethodsA meta-analysis of randomized controlled trials was conducted to evaluate the effect of oral isoflavone supplementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 62 publications
2
12
0
5
Order By: Relevance
“…Soybean isoflavones significantly reduced menopausal hot flash frequency and severity in perimenopausal and postmenopausal women, but it showed slight and slow effects in attenuating menopausal hot flashes compared with estradiol . A daily dose of more than 54 mg isoflavone could decrease the endometrial thickness for 0.26 mm . It may also improve subjective symptoms and objective signs of vaginal atrophy in menopause .…”
Section: Resultsmentioning
confidence: 95%
“…Soybean isoflavones significantly reduced menopausal hot flash frequency and severity in perimenopausal and postmenopausal women, but it showed slight and slow effects in attenuating menopausal hot flashes compared with estradiol . A daily dose of more than 54 mg isoflavone could decrease the endometrial thickness for 0.26 mm . It may also improve subjective symptoms and objective signs of vaginal atrophy in menopause .…”
Section: Resultsmentioning
confidence: 95%
“…Interestingly, a recently published meta-analysis of the clinical data found that when all studies ( n = 23; 2167 participants) were included in the analysis there was no effect of isoflavones on endometrial thickness overall whereas there was a significant ( p = 0.04) decrease in thickness when considering only the seven North American trials which involved 726 women [433]. On the other hand, there was small increase in thickness among women involved in the three Asian trials but none of these studies actually intervened with soybean-derived isoflavones.…”
Section: Effects On Endometrial Tissuementioning
confidence: 99%
“…A via transdérmica mostra menor risco de tromboembolismo venoso do estradiol quando comparado com a via oral, mostrando ser a mais segura. Por outro lado, a administração, por via oral, gera um maior impacto na redução dos níveis do colesterol LDL, o que é uma vantagem na mulher com hipercolesterolemia e triglicérides normais, levando-se em conta que o último pode elevar-se com a medicação 16,17 .…”
Section: Vias De Administraçãounclassified
“…A via de administração não oral do estradiol e da progesterona impede o metabolismo de primeira passagem pelo fígado, ocasionando, assim, menor potencial para a formação das proteínas hepáticas, fatores de coagulação e perfil metabólico, o que pode ser mais favorável em termos de riscos cardiovasculares e fenômenos tromboembólicos 15,16,17 .…”
Section: Vias De Administraçãounclassified
See 1 more Smart Citation